Fragmentation patterns and personalized sequencing of cell‐free DNA in urine and plasma of glioma patients. Issue 8 (22nd July 2021) - Mouliere, Florent; Smith, Christopher G; Heider, Katrin; Su, Jing; van der Pol, Ymke; Thompson, Mareike; Morris, James; Wan, Jonathan C M; Chandrananda, Dineika; Hadfield, James; Grzelak, Marta; Hudecova, Irena; et al.
Abstract: Glioma‐derived cell‐free DNA (cfDNA) is challenging to detect using liquid biopsy because quantities in body fluids are low. We determined the glioma‐derived DNA fraction in cerebrospinal fluid (CSF), plasma, and urine samples from patients using sequencing of personalized capture panels guided by analysis of matched tumor biopsies. By sequencing cfDNA across thousands of mutations, identified individually in each patient's tumor, we detected tumor‐derived DNA in the majority of CSF (7/8), plasma (10/12), and urine samples (10/16), with a median tumor fraction of 6.4 × 10 −3, 3.1 × 10 −5, and 4.7 × 10 −5, respectively. We identified a shift in the size distribution of tumor‐derived cfDNA fragments in these body fluids. We further analyzed cfDNA fragment sizes using whole‐genome sequencing, in urine samples from 35 glioma patients, 27 individuals with non‐malignant brain disorders, and 26 healthy individuals. cfDNA in urine of glioma patients was significantly more fragmented compared to urine from patients with non‐malignant brain disorders ( P  = 1.7 × 10 −2 ) and healthy individuals ( P  = 5.2 × 10 −9 ). Machine learning models integrating fragment length could differentiate urine samples from glioma patients (AUC = 0.80–0.91) suggesting possibilities for truly non‐invasive cancer detection. SYNOPSIS: Gliomas are challenging to detect using tumor derived cell‐free DNA (cfDNA) in body fluids. In this study, two novel analysis methods (tumor‐guided sequencing and sWGS) were developed to explore the potential of using plasma and urine cfDNA as a liquid biopsy for this malignancy. Multiple tumor regions were sequenced to recover a high number of mutations for designing tumor‐guided sequencing panels. Using tumor‐guided sequencing and the INVAR analysis approach, mutations were detected in 7/8 CSF, 10/12 plasma and 10/16 urine gliomas samples. Using low coverage whole genome sequencing, cfDNA fragmentation patterns were analysed in urine samples from 35 glioma patients, 27 individuals with non‐malignant brain disorders, and 26 healthy individuals. Fragment lengths differed significantly between these groups; Machine learning models (LR, SVM, RF, GLMEN) integrating fragment length could differentiate urine samples from glioma patients (AUC = 0.80–0.91). Abstract : Gliomas are challenging to detect using tumor derived cell‐free DNA (cfDNA) in body fluids. In this study, two novel analysis methods (tumor‐guided sequencing and sWGS) were developed to explore the potential of using plasma and urine cfDNA as a liquid biopsy for this malignancy.